Hubungan Pemenuhan Kebutuhan Dasar Manusia Dengan Kepuasan Pasien Di RSD Idaman Kota Banjarbaru - Nur Fatimah; Herry Setiawan; Ichsan Rizany (Nerspedia, 2022)
Quality of service is an important part of knowing patient satisfaction. Patient satisfaction when treated in a hospital is still in the low category. The low level of patient satisfaction is influenced by several aspects, one of which is the fulfillment of basic human needs. Inadequate fulfillment of one's needs so the services provided are not optimal and can be a problem of patient satisfaction during the treatment process.To find out the relationship between the fulfillment of basic human needs and patient satisfaction in the RSD Idaman of Banjarbaru. This research method is correlation analysis with cross sectional design and using accidental sampling technique. Data collection was carried out by administering questionnaires to 61 patients in the Idaman Regional Hospital of Banjarbaru City. The results showed that the description of meeting basic human needs an average of 80.72 and a description of an average patient satisfaction of 72.00. The results of the analysis found that there is a positive relationship between the fulfillment of basic human needs perceived by patients and patient satisfaction in the RSD Idaman of Banjarbaru . (P Value = 0,000 <0.05). Meeting basic human needs can affect the satisfaction felt by patients, so it is expected that they will improve and meet the compliance of basic needs in order to provide optimal services quality.